Child Grooming and Sexual Violence in Broken Strings: Examining Patterns of Victimization - Nurdianti, Indah; Irdina, Areezya Hana; Fareez, Arzeef Luqman; Syafiqa, Ariana Hana; Malik, Muhammad (UIR Press, 2026)
Child grooming is a manipulative process through which perpetrators establish emotional trust with children to facilitate sexual exploitation or abuse. As a covert form of sexual violence that often occurs without physical coercion, child grooming presents significant challenges for legal recognition, prevention, and prosecution. This study examines the representation of child grooming in Broken Strings by Aurelie Moeremans and analyzes the adequacy of Indonesia’s Law Number 35 of 2014 on Child Protection in addressing such conduct. Employing a normative juridical method with statutory and conceptual approaches, the study explores the patterns of grooming depicted in the narrative and evaluates the legal protections available to child victims. The findings reveal that grooming is characterized by emotional manipulation, exploitation of trust, psychological dependency, and unequal power relations, all of which constitute sexual violence despite the absence of physical contact. Although the Child Protection Law provides preventive and repressive safeguards for child victims, its implementation remains constrained by difficulties in interpreting and proving psychologically based grooming behaviors. This study contributes to the growing discourse on technology-facilitated and non-contact sexual violence by integrating literary analysis with legal evaluation, demonstrating how fictional narratives illuminate evidentiary gaps and highlighting the need for a more responsive child protection framework capable of recognizing and addressing psychological forms of sexual exploitation.